Tree Species Composition and Soil Properties in a Disturbed Rainforest Ecosystem, South-West Nigeria - Farhan Jimba Moshood; Samuel Olalekan Olajuyigbe (Forestist)
This study assessed the tree species composition and soil properties in a disturbed tropical rainforest (Osho Forest Reserve) in Nigeria. A systematic sampling method was adopted for tree species enumeration. Five line transects 1000 m long and 500 m apart were evenly distributed in the forests. Four plots (50 m × 50 m) were laid alternately and at 250 m intervals along each transect. Soil samples were collected at five points from two depths in the different land use types in the forest reserve. Twenty-four tree species belonging to 13 taxonomic families were identified. Lamiaceae had the highest tree population (190 trees). The Simpson, Shannon–Wiener, and Margalef’s indices were 0.788, 2.052, and 4.016, respectively. In the 0–15 cm depth, farmland had the highest bulk density (1.75 ± 0.33 g/cm3 ), while the secondary forest had the least (1.32 ± 0.12 g/cm3 ). Secondary forest had the highest organic carbon content (2.80 ± 0.49%) while farmland had the least (0.95 ± 0.33%). The soil organic carbon content of secondary forest was significantly different from other land uses. In the 15–30 cm depth, farmland had the highest bulk density (1.79 ± 0.65 g/cm3 ), while Tetrapleura tetraptera plantation had the least (1.41 ± 0.54 g/cm3 ). Secondary forest had the highest organic carbon content (2.12 ± 0.75%), while farmland had the least (0.65 ± 0.10%). However, organic carbon did not significantly differ across land use types, except for secondary forest. The textural class in all the land use types was loamy sand. The study concludes that Osho Forest Reserve requires an immediate, intensive, and encompassing intervention to achieve restoration and rehabilitation.